Experiences of identity development and sexual stigma for lesbian, gay, and bisexual young people in sport: 'Just survive until you can be who you are'. Issue 2 (15th March 2018) - Petty, Lisa; Trussell, Dawn E.
Abstract: This interpretive study sought to critically examine how the coming-out process for young people who identify as lesbian, gay and bisexual (LGB) shaped their sport engagement. Using an evocative inquiry framework and stories as a form of knowledge and representation, the perspectives of nine participants from Canada and the United States were examined. Emphasis is placed on how sexual stigma shaped their sport involvement and meanings, the emotionality of their experiences, and the social relationships therein. The findings call attention to the complicated connection that LGB young people have with sport as they develop their sexual identities through the coming-out process while experiencing sexual stigma.